Seeking professional help for sleep-related complaints - Rauch, Lisa; Schneider, Torsten; Wendt, Claus (Frontiers in Public Health, 2024)
IntroductionSleep-related complaints affect a significant proportion of the adult population in many societies. Despite the prevalence of symptoms and potential secondary and comorbid conditions, the utilization of professional help is quite low. The underlying reasons for this phenomenon have yet to be adequately investigated. To address this gap, we expand the conventional explanatory models to encompass the perceived cause as an explanatory factor. This is aimed to contribute to a better understanding of the help-seeking behavior and to create the basis for possible measures.Materials and methodsThe empirical basis of the study is a quantitative data set collected in Germany in 2015 comprising 3,000 individuals between the ages of 40 and 75. Of these individuals, 761 reported experiencing sleep-related complaints. In our logistic regression, the binary dependent variable is whether professional help has already been sought. In addition to the factors included in the behavioral model of health service use, we utilize the perceived cause as a predictor, categorizing the variable as follows: exclusively mental, partially mental, and not mental.ResultsOur analysis shows that individuals who attributed their sleep disturbances solely to their psyche were significantly less likely to seek professional help (AME: −0.158**). These differences remain significant after controlling for the severity of the complaints, their duration, and other covariates (AME: −0.117**). The data also suggest that this group is more likely to seek self-help through medication.DiscussionThe results indicate the importance of focusing healthcare systems and public health policy on sleep-related complaints and their management. The aim is not only to alleviate sleep complaints, but also to reduce the risk of secondary diseases and to identify possible comorbidities. Additionally, it is a factor in reducing safety risks for the general public. Therefore, various measures should be implemented, including destigmatizing, improving health literacy, a more comprehensive offer of cognitive-behavioral therapy (CBT-I), and a more thorough examinations by physicians.